2023
DOI: 10.1371/journal.pbio.3001778
|View full text |Cite
|
Sign up to set email alerts
|

TXNIP loss expands Myc-dependent transcriptional programs by increasing Myc genomic binding

Abstract: The c-Myc protooncogene places a demand on glucose uptake to drive glucose-dependent biosynthetic pathways. To meet this demand, c-Myc protein (Myc henceforth) drives the expression of glucose transporters, glycolytic enzymes, and represses the expression of thioredoxin interacting protein (TXNIP), which is a potent negative regulator of glucose uptake. A Mychigh/TXNIPlow gene signature is clinically significant as it correlates with poor clinical prognosis in triple-negative breast cancer (TNBC) but not in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Lim et al [ 23 ] discovered that TXNIP loss increases MYC-dependent gene expression by increasing Myc genome occupancy in several types of cells rather than by directly affecting MYC protein expression. Consistent with the findings of Lim et al [ 23 ], it was observed that knocking down Txnip in NP cells did not significantly alter the expression of MYC (Fig. 5 g; Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lim et al [ 23 ] discovered that TXNIP loss increases MYC-dependent gene expression by increasing Myc genome occupancy in several types of cells rather than by directly affecting MYC protein expression. Consistent with the findings of Lim et al [ 23 ], it was observed that knocking down Txnip in NP cells did not significantly alter the expression of MYC (Fig. 5 g; Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MYC directly promotes the cellular uptake of glutamine by increasing the transcription of SLC1A5 (the main glutamine transporter) through the enhancer box (E-box, CACGTG) [ 26 ]. Intriguingly, Lim et al [ 23 ] reported that MYC-dependent genes affected by TXNIP loss are highly and significantly enriched for canonical CACGTG MYC-binding E-boxes. Our transcriptomic analysis also revealed a significant upregulation of Slc1a5 expression in response to mannose (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, metabolic stress activates metabolic sensors, such as MondoA, which is able to reduce glucose uptake and aerobic glycolysis via induction of thioredoxin-interacting protein (TXNIP) [ 135 , 136 ]. TXNIP activation decreases the genome occupancy of MYC, thereby inhibiting its transactivating function [ 137 ]. However, the functional relationship between MYC and MondoA is tumor type-specific and influenced by altered MYC levels.…”
Section: Conclusion and Potential Therapeutic Aspectsmentioning
confidence: 99%